2018
DOI: 10.1038/nbt.4202
|View full text |Cite
|
Sign up to set email alerts
|

Genome editing of upstream open reading frames enables translational control in plants

Abstract: Translational regulation by upstream open reading frames (uORFs) is becoming established as a general mechanism for controlling the amount of protein that is synthesized from downstream primary ORFs (pORFs). We found that genome editing of endogenous uORFs in plants enabled the modulation of translation of mRNAs from four pORFs that are involved in either development or antioxidant biosynthesis. A single-guide RNA that targeted the region harboring a uORF initiation codon can produce multiple mutations. Follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
174
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 271 publications
(181 citation statements)
references
References 33 publications
4
174
0
3
Order By: Relevance
“…Several studies have illustrated the power of altering mRNA translation via uORFs to improve agriculture (13). For example, engineering rice that specifically induces defense proteins when a uORF is repressed by pathogen attack enables immediate plant resistance without compromising plant growth in the absence of pathogens (2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have illustrated the power of altering mRNA translation via uORFs to improve agriculture (13). For example, engineering rice that specifically induces defense proteins when a uORF is repressed by pathogen attack enables immediate plant resistance without compromising plant growth in the absence of pathogens (2).…”
Section: Discussionmentioning
confidence: 99%
“…Besides being an essential step in gene expression, mRNA translation directly shapes the proteome, which contributes to cellular structure, function, and activity in all organisms. The characterization of translational regulation has enabled crop improvement, including increasing tomato sweetness, rice immunity and lettuce resistance to oxidative stress (13). However, due to limited genomic resources and methods, most crop translatomes remain understudied.…”
Section: Introductionmentioning
confidence: 99%
“…Since its demonstration in plants in late 2013 (Li et al ., ; Nekrasov et al ., ; Shan et al ., ), CRISPR‐Cas9 has been widely applied in many plant species (Malzahn et al ., ; Yin et al ., ). Most studies have relied on non‐homologous end joining (NHEJ) DNA repair pathway to introduce insertion or deletion (InDel) mutations, achieving editing outcomes such as gene knockout (Malzahn et al ., ), mutagenesis of microRNAs (Zhou et al ., ) or cis ‐regulatory sequences (Rodriguez‐Leal et al ., ; Zhang et al ., ), as well as large chromosomal deletions (Zhou et al ., ) and gene replacement (Li et al ., ). In some cases, homology directed repair (HDR) was used for targeted gene replacement (Endo et al ., 2016b; Gil‐Humanes et al ., ; Li et al ., ; Miki et al ., ; Schiml et al ., ; Svitashev et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Upstream ORF could inhibit the translation initiation rate of downstream CDS regions by retaining or dissociating ribosomes from mRNA. A short ribosome‐encoded peptide interacts with the ribosome to induce the arrest of the ribosome located on the initiation codons of uORFs to the terminator, which affects the translation of downstream CDS . Two studies reported that the presence of uORFs of 25 codons in the 5′UTR region of CPA1 mRNA, which encodes a fungal AAP that regulates ribosome function.…”
Section: Discussionmentioning
confidence: 99%
“…A short ribosome-encoded peptide interacts with the ribosome to induce the arrest of the ribosome located on the initiation codons of uORFs to the terminator, which affects the translation of downstream CDS. 33 Two studies reported that the presence of uORFs of 25 codons in the 5′UTR region of CPA1 mRNA, which encodes a fungal AAP that regulates ribosome function. Ribosomal retention of AAP at the stop codon, which is induced by increasing arginine, inhibits the translation of CPA1.…”
Section: Discussionmentioning
confidence: 99%